Strategic supplier selection: the importance of process formality in non-automated supplier selection decisions. Issue 1 (31st December 2022) - Woschank, Manuel; Dallasega, Patrick; Zunk, Bernd M.; Pacher, Corina
Abstract: Industry 4.0 mainly focuses on the application of modern technologies (digitalization) and the changing role of human beings (digital transformation) in modern production and logistics systems. Besides the basic principles of digitalization, interconnectivity, and autonomization, the importance of human-centered decision-making processes, such as the selection of strategic suppliers, is also increasing, as complex, novel, and unstructured decisions cannot be fully computerized. In this context, there is still a lack of understanding of which formal patterns in the strategic supplier selection process will lead to better supplier performance. Until now, most of the literature emphasizes a minor number of process-related factors in the strategic supplier selection process leading to limited support for the individual decision-maker. This study introduces a cause-effect model that extends prior research by investigating the impact of process formality, as a comprehensive measurement construct of target-, information-, organization-, and heuristics-related process factors in the strategic supplier selection process on supplier performance and purchaser satisfaction. Based on the usage of variance-based structural equation modeling in a large-scale field study, a significant relationship between process formality and supplier performance as well as between process formality and purchaser satisfaction is substantiated.